Desenvolvimento de misturas ternárias para remoção de reboco de fluido de perfuração sintético - Pinheiro, Francisca Sheldakelle Holanda Torres (2013)
The construction of wells is one of the most important activities of the oil industry. The drilling process is the set of activities and operations to design, program and perform the opening thereof. During this process, the cuttings are removed by the drilling fluid, or mud, and carted to the surface. This fluid is injected into the drill string and returns to the surface through the annular space between the well walls and the drill string. After the descent of the column casing, the annular space between the casing string and the walls of the borehole is filled with cement so as to secure the spine and prevent any migration of fluids between the various permeable zones traversed by the well behind of the coating. To ensure the good quality of the cementation scrubbers are used mattresses which are pumped ahead of the cement slurry so as to avoid contamination of the drilling fluid paste, or vice versa, and assist in the removal of plaster, formed by drilling fluid of the borehole walls, thus enabling a better cement bond to the well. Within this context, this work aims to evaluate the efficiency of mattresses scrubbers, the basis of ionic and nonionic surfactants, on the removal of nonaqueous drilling fluid, based on n-paraffin in oil wells, and the compatibility between the Mattress relations washer / drilling fluid bed scrubber / cement paste mattress washer / cement slurry / drilling fluid and the drilling fluid / cement slurry using laboratory tests rheology, thickening time and compressive strength. Also technique was performed X-ray diffraction (XRD) for a more detailed analysis of these mixtures with hydrated cement paste. In compatibility tests the conditions of temperature and pressure used in the same laboratory procedure simulating the conditions of oil wells, the well is considered the depth of 800 m. The results showed that the compositions of the mattress washer nonionic, KMS obtained a 100% efficient in removing the non-aqueous drilling fluid, and the best formulation showed good results with respect to compliance testing